DESIGN AND ANALYSIS CONTRA ROTATING PROPELLER IN TORPEDO WITH LARRABEE DESIGN METHOD AND NUMERICAL SIMULATION - Irawan Prihatmadi - Nim: 13614072 , Luthfi
This final project report discuss about contra rotating propeller design using larrabee design method and numerical analysis. The result of contra rotating propeller design is for torpedos thruster. Contra rotating propeller have many advantages over single propeller, smaller diameter and lower loading for every blade, total torque is balanced due to the opposite rotation of the forward and aft propeller, and also energy lost in slipstream recover by the aft propeller. The analytic calculation for contra rotating propeller with larrabee design is added by uncoupled method. Uncoupled method is contra rotating propeller design methods which neglect the relationship between forward and aft propeller in axial gap function. The effect of axial gap due to the relation between forward and aft propeller is analyze with numerical simulation using CFD. To get the total torque is balanced in specific thrust, the effect of axial gap is become the important parameter. Beside desire thrust and total torque balanced achieved, contra rotating propeller design should not occur cavitation phenomenon when it operate in underwater, because cavitation cause the efficiency decrease and increase the noise of the propeller.